Identifying leverage points and levers to reduce normative constraints in agrifood systems in Tanzania and Nigeria - Mwakanyamale, Devis; Msita, Sarah; Cole, Steven; Adeyeye, Olajumoke; Seymour, Greg; Ferguson, Nathaniel; Feleke, Shiferaw; Jeremiah, Adolf; Rietveld, Anne; Mudege, Netsayi; Achandi, Esther; Costenbader, Elizabeth; et al. (CGIAR Initiative on Gender Equality, 2024)
The Harnessing Gender and Social Equality for Resilience in Agrifood Systems (HER+) Initiative (known also as the Gender Equality Initiative) seeks to transform agrifood systems (AFSs) by addressing structural gender inequalities such as harmful social and gender norms. Such norms within AFSs can impede the building of women’s economic resilience, increasing their vulnerability to the impacts of climate change. The Initiative seeks to transform AFSs using gender transformative approaches (GTAs) that help women become more economically resilient.